A Unique Case of Allogeneic Fat Grafting Between Brothers. Issue 9 (September 2016) - Kim, Samuel; Edelson, Richard L.; Sumpio, Brandon; Kwei, Stephanie; Narayan, Deepak
Abstract : Summary: We present a case of a 65-year-old man with cutaneous T-cell lymphoma treated with radiation therapy and an allogeneic hematopoietic stem cell transplant from his human leukocyte antigen-matched brother. Engraftment was successful, but the patient went on to develop painful, radiation-induced ulcers. The ulcers were fat-allografted using liposuctioned fat from his brother because of the patient's unique chimeric state. Postprocedure follow-up revealed epithelialization of the ulcer sites and significant improvement in neuropathic pain. Our unique case study supports the use of fat grafting for its restorative purposes and for its ability to alleviate chronic neuropathic pain. Additionally, it appears that our case provides a basis of a general approach to the treatment of radiation-induced ulcers in chimeric patients with lymphoid malignancies. Abstract : Supplemental Digital Content is available in the text.